(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
The Extension and Professional Practice Center (NEPP) is an initiative of the Federal Institute of Rio Grande do Norte (IFRN) as a way of linking academic knowledge with the different actors in society. On the Caicó campus, in the interior of the state, the NEPP was founded in 2017, offering continuing education courses for women in situations of social vulnerability, to engender a profession, entering the job market. In addition, the nucleus still allows the development of the professional practice of students of the higher technology course in Fashion Design. This paper aims to expose and discuss the institutional actions and the impact of NEPP between 2021 and 2022 on the local sociocultural scenario. For that, the action research method was used, with qualitative verification of the objectives. In this way, a course on embroidery techniques was offered, an important regional element, revitalizing local work. Allied to this, a scenario was provided for the development of a fashion collection by undergraduate students, employing such a handcrafted motif in its configuration, using embroidery students as labor. The collection, therefore, was intended to serve as a showcase for the work of women in situations of social vulnerability. As a result, the workshops lasted four (4) days. In the meantime, the students enrolled in the embroidery course were surprised by the quick way they learned to embroider.